Influence of the obligate parasite Cuscuta campestris on growth and biomass allocation of its host Mikania micrantha - Shen, Hao (Journal of experimental botany, 2005)
As a means of biologically controlling Mikania micrantha H.B.K. in South China, the influence of the obligate parasite Cuscuta campestris Yuncker on its growth and biomass allocation was studied using pot trials. The effect of C. campestris on M. micrantha became greater with time, such that the host biomass was only 1.8% of the control after 60 d of parasitism and by day 72 almost all the aerial parts of the host plants had died. Afterwards, the hosts and the remnant parasite shoots re-grew but the total biomass of the hosts was still significantly lower than that of the controls. The infection by C. campestris greatly increased the shoot:root dry weight ratio and the allocation to stems of the infected plants from 40 to 50 d after parasitization, but decreased their relative growth rate and unit leaf rate starting from 20 d after parasitization and their leaf area ratio from 30 to 60 d after parasitization. Cuscuta campestris significantly reduced the total biomass, changed the biomass allocation patterns, and completely inhibited the flowering of the infected M. micrantha plants. These results indicate that the use of C. campestris could be a potentially effective way of controlling M. micrantha